The influence of rosuvastatin on liver microsomal CYP2C6 in hereditary hypertriglyceridemic rat - Vecera, Rostislav; Zacharová, Alice; Siller, Michal; Matuskova, Zuzana; Skottová, Nina; Anzenbacherová, Eva; Anzenbacher, Pavel (Neuro endocrinology letters, 2012)
OBJECTIVES: The aim of this study was to investigate whether rosuvastatin affects expression and activity of rat CYP2C6. This cytochrome P450 is considered to be a counterpart of human CYP2C9, which metabolizes many drugs, including diclofenac, ibuprofen or warfarin. DESIGN: Male hereditary hypertriglyceridemic (HHTg) rats were fed standard laboratory diet (STD) or high cholesterol diet (HCD: STD + 1% of cholesterol w/w + 10% of lard fat w/w) for 21 days. A third group of rats were fed high a cholesterol diet with rosuvastatin added (0.03% w/w). Expression of CYP2C6 was measured in liver samples using real-time PCR (mRNA level) and Western blotting (protein level). Formation of diclofenac metabolites (typical enzyme activity of CYP2C6) was analyzed using HPLC with UV detection. RESULTS: Administration of rosuvastatin to HHTg rats resulted in significantly increased mRNA expression and enzyme activity in HCD-fed animals; changes of CYP2C6 protein were non-significant. These results suggest that CYP2C6 expression and activity are positively affected by rosuvastatin in hereditary hypertriglyceridemic rats after intake of HCD. CONCLUSION: The results presented open the possibility that in humans, rosuvastatin may affect the metabolism of many drugs by influencing expression and activity of CYP2C6 (counterpart of human CYP2C9). Further studies are needed to elucidate the effects of this statin on CYP2C9 in humans.
Keywords: hyperlipoproteinemie typ IV; genetická transkripce; fluorbenzeny; steroid-21-hydroxylasa; jaterní mikrozomy; statiny; Microsomes, Liver; Hyperlipoproteinemia Type IV; Humans; Cytochrome P450 Family 2; rosuvastatin kalcium; aromatické hydroxylasy; messenger RNA; pyrimidiny; regulace genové exprese enzymů; Transcription, Genetic; Hydroxymethylglutaryl-CoA Reductase Inhibitors; cholesterol dietní; sulfonamidy; mutantní kmeny potkanů; Aryl Hydrocarbon Hydroxylases; krysa rodu Rattus; lidé; Rats, Mutant Strains; zvířata; Steroid 21-Hydroxylase; potkani Wistar; Rosuvastatin Calcium; Cytochrome P-450 CYP2C9; cytochrom P450 CYP2C9; RNA, Messenger; Fluorobenzenes; Rats, Wistar; Male; rodina 2 cytochromů P450; Rats; Gene Expression Regulation, Enzymologic; Animals; Pyrimidines; mužské pohlaví; Cholesterol, Dietary; Sulfonamides